2008
DOI: 10.1063/1.3040003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of pentacene-fullerene heterojunctions

Abstract: In this study the performance differences of layered and bulk-heterojunction based organic solar cells composed of the prototypical p-and n-type organic semiconductors pentacene ͑PEN͒ and fullerene ͑C60͒ are correlated with the physical properties of the heterostructures. The electronic structure of layered and codeposited thin PEN and C60 films on the conducting polymer substrate poly͑ethylenedioxythiophene͒:poly͑styrenesulfonate͒ ͑PEDOT:PSS͒ was investigated with ultraviolet photoelectron spectroscopy. Layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 67 publications
9
105
1
Order By: Relevance
“…Accordingly, the present findings of the absence of the vacuum level shift and band bending are consistent with the theoretical predictions. Taking into consideration that the "head-on" orientation is thought to be dominant in the pilot OPV devices with a planar pentacene-C 60 heterojunction [40], which was reported to yield rather better power conversion efficiency than mixed heterojunction OPVs consisting of this materials' combination [15], the present results obtained at a structurally well-defined molecular heterointerface provide realistic insights into electron energetics in the pentacene-C 60 OPV devices.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Accordingly, the present findings of the absence of the vacuum level shift and band bending are consistent with the theoretical predictions. Taking into consideration that the "head-on" orientation is thought to be dominant in the pilot OPV devices with a planar pentacene-C 60 heterojunction [40], which was reported to yield rather better power conversion efficiency than mixed heterojunction OPVs consisting of this materials' combination [15], the present results obtained at a structurally well-defined molecular heterointerface provide realistic insights into electron energetics in the pentacene-C 60 OPV devices.…”
Section: Resultsmentioning
confidence: 91%
“…They proposed ∆ DA of 1.56 eV and an upward vacuum level shift of 0.36 eV toward the C 60 side. Salzmann and co-workers studied this bi-molecular systems on a conductive polymer film to find the gap width of 1.15 eV and an absence of the vacuum level shift [15]. However, since reported V oc values for this molecular combination is less than 0.5 eV [35], even if an energy conversion loss of 0.3 − 0.5 eV [36,37] due to the binding energy of the electron-hole pairs is taken into account, the ∆ DA values of these previous works may be overestimated to explain the practical systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option, however, is the creation of ''multi-heterojunction'' cells where two or more donors are deposited in contact with an acceptor which provides for exciton dissociation and photocurrent production from two or more O/O 0 heterojunctions in parallel. [136,246,247] A third option being explored is to use thin layers of donors and acceptors arranged to promote both vectoral flow of spectral energy and charge flow, from one donor to the other, while broadening the spectral response of the OPV. Figure 6 shows the first step in this process with the 60 , pentacene/C 60 , and pentacene/TiOPc/C 60 heterojunctions.…”
Section: For Many O/omentioning
confidence: 99%
“…[19,26,34,52,72,134,135] For both bulk heterojunction (BHJ) polymer OPVs, and small molecule PHJ OPVs, it has been observed that the molecular environment can have a significant effect on these energies, helping to control the probability for photocurrent production. [23,136,137] The power conversion efficiency, h, of an OPV is ultimately determined by the product of V OC and the J SC , and by the fill-factor (FF) ( Figure 1C):…”
mentioning
confidence: 99%